Optimization Of Discharge Planning Implementation by Giving Media Leaflet to Patients Discharging in the Internal Disease Room RSUD Raden Mattaher Jambi - Mawarti, Indah; Gini, Susang (Jurnal Pinang Masak, 2025)
Background: Discharge planning is a nursing process that should be carried out continuously and started as soon as possible when the patient is admitted to the hospital, when the patient is being treated until the follow-up plan. Method: case study report with observation and interviews. Analysis: implementation was carried out for 4 days, where the leaflet making process was carried out together with the hospital's health promotion for 3 days and the submission of leaflets to the room head and the implementation of health education for patients who were going home were carried out for one day. Results: leaflets were available in the inpatient ward and the provision of educational media was carried out during the implementation of health education. Conclusion: during the implementation of discharge planning, nurses gave several leaflets to patients and families. Discharge planning using educational media in the inpatient ward of internal medicine at Raden MattaherJambi Hospital.